Atypical Dengue Outbreak in Odisha: Insights from the Entomological Investigations - Sudhansu Sekhar Sahu; Mohammed Mustafa Baig; Dilip Kumar Panigrahi; Ananganallur Nagarajan Shriram; Ashwani Kumar (Indian Journal of Public Health, 2024)
An outbreak of dengue fever struck Tikarapada village, Rayagada district (April 2020). Among 117 fever cases, 49 tested positive for the dengue NS1 antigen. To identify mosquito-related factors in the outbreak, a survey of 101 houses found Aedes breeding sites in 11.6% of containers. Aedes aegypti (79%) and Aedes albopictus (21%) emerged from collected pupae. The village exhibited high (house index = 24.8), (container index = 11.6), (pupal index = 32.7), and (Breteau index = 40.6) indices. The findings confirmed the presence of Aedes and ample breeding sites, suggesting their role in the outbreak. A report recommending integrated vector control measures was submitted to district and state health authorities.